2017
DOI: 10.2147/jpr.s123554
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception about medication sharing among patients: a focus group qualitative study on borrowing and lending of prescription analgesics

Abstract: BackgroundOne form of self-medication is sharing of medications, defined as borrowing or lending medications in situations where the receiver of these drugs is not the individual to whom the medications were allocated.ObjectiveTo explore experiences and opinions of patients about sharing prescription analgesics, reasons for sharing prescription analgesics, the way in which patients choose to share those medications, their awareness of risk regarding sharing prescription analgesics, and how they estimated the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…Consistent with previous studies, painkillers, antibiotics and allergy medicine were the most frequently borrowed and lent medicines . This is possibly because, in Saudi Arabia, allergy medications and some pain medications are easily accessible and can be obtained either with or without a prescription over the counter (OTC).…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with previous studies, painkillers, antibiotics and allergy medicine were the most frequently borrowed and lent medicines . This is possibly because, in Saudi Arabia, allergy medications and some pain medications are easily accessible and can be obtained either with or without a prescription over the counter (OTC).…”
Section: Discussionsupporting
confidence: 86%
“…immediate family, wider family, friends or acquaintances, colleagues from work, neighbours and other persons), while for the seventh answer, respondents could indicate any other person not mentioned in the first six choices. We believe that this might have contributed to a higher reported prevalence of prescription analgesic sharing because our previous qualitative study regarding this same subject showed that patients did not necessarily believe that sharing medication with immediate family was a problem, and even perceived prescription medications as a common property of a family (Markotic et al., ).…”
Section: Discussionmentioning
confidence: 97%
“…Negative aspects include delayed seeking of medical care, increased risk of side effects, health complications associated with incorrect medication or multiplied risk of developing resistance to medication (Goldsworthy and Mayhorn, ; Dimitrov et al., ; Beyene et al., ). Justifiable aspects of this behaviour, as described in literature, include situations where medical aid is unavailable, inconvenience associated with contacting a physician, saving money, lack of faith in physicians, helping patients cope with pain, accessibility of drugs in pharmacies, availability of medication provided by close individuals and maintaining good interpersonal relationships (Hodgetts et al., ; Kamutingondo et al., ; Beyene et al., ; Markotic and Puljak, ; Markotic et al., ). Nonrecreational sharing of medication is mostly motivated by the desire to help others or oneself (Kamutingondo et al., ; Markotic et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that the patients are self-medicating and sharing analgesics between themselves to alleviate pain. It is known that sharing of even prescription analgesics is a common behavior that is viewed positively by patients and even some physicians 20,21…”
Section: Discussionmentioning
confidence: 99%